Accuracy of SIRS, age-adapted pSOFA, and quick SOFA scoring systems for predicting outcomes in paediatric patients with sepsis: a meta-analysis - Jingmin Sun; Jing Li; De Wu; Fang Deng (Elsevier, 2022)
Background: Sepsis is the leading cause of mortality in children. Several scoring systems are used to predict outcome and mortality for pediatric patients with sepsis, but how they compare to each other in terms of sensitivity and specificity is unclear. Methods: The systematic literature review was performed following PRISMA guidelines. Publically accessible search engines and study databases such as PubMed, CENTRAL (Cochrane Central Register of Controlled Trials), and Google Scholar were scanned for articles published from January 1990 to March 2021 using relevant key words. All relevant studies were analyzed separately by two reviewers. A random-effects model was used to calculate the pooled sensitivity and pooled specificity with a 95% confidence interval (CI). Heterogeneity was evaluated using I2, which estimates the percentage of variation between study results due to heterogeneity rather than sampling error. Results: Eleven studies met inclusion criteria and evaluated the SOFA scoring system. The pooled sensitivity, specificity, and SROC for prediction of mortality were 83% (95% CI: 76%-88%), 72% (95% CI: 60%-81%), and 85% (95% CI: 82%-88%), respectively. Six studies examined the SIRS system. Pooled sensitivity, specificity, and SROC were 80% (95% CI: 64%-90%), 36% (95% CI: 23%-51%), and 59% (95% CI: 55%-63%), respectively. Conclusion: This meta-analysis shows that SOFA was superior to SIRS for predicting mortality in PICU patients with sepsis. Additional prospective multi-centric studies are needed to better evaluate and validate this finding.